PENGEMBANGAN ”LEISURE AND RECREATION FOR LATER LIFE” (WISATAWAN LANJUT USIA) DI KAWASAN WISATA SANUR-BALI - Maharani Suarka, Fanny; Sri Sulistyawati, Agung; Ratna Sari, Ni Putu (Jurnal Analisis Pariwisata, 2018)
The aim of this research is to develop the leisure and recreation model for later life at Sanur Bali by identified the later life tourist at this object. The background of this resarch is the existence of the later life tourist at Sanur, nowdays Sanur has been developed rapidly but Sanur is still chosen by this age segmen. 50 person which are the later life tourists are choosen as the respondent in this study, they come from Europe and Australia. Their travel is organized by themselves and they come with their couple in spending their leisure. The data collected by depth interview, questionaires and documentation study. At Sanur, later life tourists can be met mostly at southern part of Sanur along Danau Toba and Tamblingan street. Adventure and Playing are the activities that are not choosen by this age to do. The later life tourists perception generally at good range toward the later life activities, the entertainment, and also for the theme of entertainment at their hotel to stay. Happy Passive and healthy Leisure Model are recomended as the result of this research. The improvement standardization for the later life age is recomended program for public tourist facilities and also at the hotel, restoran and cafe is the recomnded strategy for maintaining the existence of Sanur as the tourist destination for the later life tourist.